Communication Management in Local Government: Crisis Communication Strategies and Public Relations - Syailendra Reza Irwansyah Rezeki; Julia Magdalena Wuysang; Muhamad Hidayat; E. Rizky Wulandari; Muhamad Teguh Setiadi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This article discusses the vital role of communications management in the local government context, focusing on crisis communications strategies and community relations. This research aims to evaluate the effectiveness of local government communication practices in dealing with crises and in establishing good relationships with local communities. Research methods involve interviews with public relations practitioners and stakeholders and online surveys to gather community views. The research results show that local governments have positively tried to convey information, respond quickly, and listen to citizens' views during crises. However, there is still room for improvement, especially in technology such as virtual meetings and text messaging. These findings provide valuable insights into communication management practices in local government and their implications for building transparent and responsive government.